Improvement of Mechanical Properties of Self-sealing Material of Self-sealing Fuel Tank by Adding Nanocellulose Fiber - Kanithasungkas, Yanasorn; Sornsuwan, Sedtawut; Panmee, Aegwat; Isarankura Na Ayutthaya, Siriorn (Journal of Advanced Development in Engineering and Science, 2023)
This research concerns the improvement of the strength of natural rubber. The nanocellulose fiber were used as reinforcement in natural rubber at 0, 2, 4, 6, 8 and 10 phr, which can be used as a self-sealing material of the self-sealing fuel tanks. This research studied the porosity content, mechanical properties (before and after gasoline uptake) and the rate of rubber swelling. Preparation process, the nanocellulose fiber and distilled water were mixed, and the fiber was dispersed by using a high frequency ultrasonic probe. Afterwards, the fiber solutions and the natural rubber latex were mixed by using a magnetic stirrer and dried in an oven at 70 oC for 12 h. Then, the masterbatches of the fiber/rubber were blended with the natural rubber and the additives using a two-roll mill machine. Afterward, the compounds were measured the curing time (tc90) using the oscillating rheometer at 150 degree celsius. The compounds were fabricated to be the samples in a sheet form, using the hot-press compression molding machine. Subsequently, the samples were studied the morphology, including the porosity content and the fiber distribution by using the scanning electron microscopy. The mechanical properties were tested by using the universal testing machine. Meanwhile, the samples were immersed into the gasoline. The rate of rubber swelling at various times were investigated. The results conclude that the rubber sheet with 2 phr of the nanocellulose fiber is the optimum formula. It was due to this formula stronger than the neat rubber, before and after gasoline uptake. Furthermore, it also has the highest rate of swelling.